Um serviço para flexibilização da tarifação em nuvens de infraestrutura - Viana, Nayane Ponte (2013)
Cloud computing has emerged in 2006 with the idea to make the utility computing service. This new paradigm is based on several mature technologies that have come to the right time, such as grid computing, distributed systems and virtualization. However, cloud computing has its peculiar features, like customization, elasticity and pay-per-use service and, moreover, to be a new paradigm, has many open questions that needs to be mature, such as security, availability and charging. The pricing is a key feature of cloud computing. In this approach the customer pay for your use, model known as pey per use. Then, perform the monitoring of the resources use is needed in order to pricing. In cloud services infrastructure case, monitoring the hardware resources use is necessary. However, many academic studies show that the form of charging by cloud providers do not take into account important requirements for the customers invoice calculation. Based on this, this work aims to improve the flexibility of charging for infrastructure clouds. For this, an academic and industry study was made to collect and sort the requirements for flexible charging services in cloud computing. Thus, an architecture and service charges, the aCCountS (a Cloud Accounting Service) and a domain specific language (DSL) for defining pricing policies in clouds, called Accounts-DSL, was proposed. In this study are defined: (i) the service architecture and the description of its key parts, (ii) the accounting service proposed and how it was developed, and (iii) the charging language and its requirements and grammar. Finally, the experimental evaluation performed to test the correctness of the service and the language proposed are described. For this, real test was made with the service deployment in commercial clouds in order to test the aCCountS and aCCountS-DSL features.